Hipossalivação e seus fatores de risco em idosos funcionalmente independentes e não institucionalizados - Souza, Altaíva Jales Costa (2007)
The aim of this study was to investigate the risk factors related to hyposalivation among non-institutionalized independently living elderly people, living in Natal-RN, Brazil. The study was a control-case type and the data collection was accomplished by carrying a questionnaire, oral examination and a non-stimulated and stimulated sialometry. The cases were identified by values of salivary flow rate <0,1mL/min and stimulated ≤ 0,5 mL/min, and the controls were by observing the values of sialometry that were bigger than the previously defined parameters. Age and gender were used as pairing variables. The data were analyzed using X2 (α = 0,05) and odds ratio. The sample was composed of 98,1% female and 1,9% male, with mean age 68. There was not association between hyposalivation and the following studied variables: income, schooling, profession, dwelling conditions, domiciliary density, illness, number of teeth and use of prothesis. However, a link was found between hyposalivation and smoking frequency in the passet (OR=5,14), indicating that, referring to elderly people, the tabagism frequency habit was a risk factor to the studied condition. Therefore, refering to non-institutionalized independently elderly people, economic-social-demographic conditions, general and bucal health, diet and habits such as alcoholism have been not risk factors to hyposalivation. However, people that have been smoking have more risk to have the studied conditions